2014
DOI: 10.1002/2014gl059294
|View full text |Cite
|
Sign up to set email alerts
|

Lunar-solar interactions in the equatorial electrojet

Abstract: To first order the ground magnetic signature of the equatorial electrojet (EEJ) reflects the height integral of J = E, where is a conductivity and E represents some combination of the global dynamo-generated electric field and the electric field due to local winds. Day-to-day variations in the conductivity are strongly controlled by the solar flux, while E depends on solar and lunar tides, planetary waves, and the disturbance dynamo. In this study we demonstrate how complexity is introduced into the EEJ due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…According to numerical simulations, that pattern could be also due to a phase shift in the solar semidiurnal tide [e.g., Pedatella and Liu , ]. The presence of M 2 during SSWs has been also reported from other ground‐based observations as well as in situ observations on‐board satellites [e.g., Stening , ; Gasperini and Forbes , ; Lühr et al , ; Park et al , ; Yamazaki et al , ; Yamazaki , , ; Yamazaki and Kosch , ; Zhang et al , ]. Lunar tides in the ionosphere have been observed at other times, but their amplitudes are much smaller than at times of SSWs, i.e., northern hemispheric winter [e.g., Bartels , ; Chapman and Lindzen , ; Matsushita , ; Stening and Fejer , ; Stening and Rastogi , ; Pedatella and Forbes , ; Aveiro and Hysell , ; Eccles et al , ].…”
Section: Introductionmentioning
confidence: 73%
“…According to numerical simulations, that pattern could be also due to a phase shift in the solar semidiurnal tide [e.g., Pedatella and Liu , ]. The presence of M 2 during SSWs has been also reported from other ground‐based observations as well as in situ observations on‐board satellites [e.g., Stening , ; Gasperini and Forbes , ; Lühr et al , ; Park et al , ; Yamazaki et al , ; Yamazaki , , ; Yamazaki and Kosch , ; Zhang et al , ]. Lunar tides in the ionosphere have been observed at other times, but their amplitudes are much smaller than at times of SSWs, i.e., northern hemispheric winter [e.g., Bartels , ; Chapman and Lindzen , ; Matsushita , ; Stening and Fejer , ; Stening and Rastogi , ; Pedatella and Forbes , ; Aveiro and Hysell , ; Eccles et al , ].…”
Section: Introductionmentioning
confidence: 73%
“…It is well known that F10.7 exhibits an evident 27-day periodicity throughout the year due to the 27-day rotation of the Sun (Takahashi et al, 2010;Gasperini and Forbes, 2014). As the mesopause is the coldest region in the atmospheric temperature profile, it is impossible for the strong quasi-27-day oscillation in the MLT observed by meteor radar to be driven through direct absorption of solar radiation in the local region though the oscillation in the zonal wind near the mesopause is in phase with that in F10.7, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the effect of the semi-monthly lunar tide (= 14.77 days) can easily alias into the 16-day spectrum, especially when the amplitude and phase of the lunar tide are changing with time, such as during stratospheric sudden warming events. Furthermore, Gasperini and Forbes (2014) showed that the combined effect of solar rotation (= 27 days) and lunar tide (= 14.77 days) can cause sideband frequencies corresponding to 9.55-and 32.61-day periods. Love and Rigler (2014) also found various spectral components within the 2-16 day range that arise from solar and lunar tides and intermodulations among them.…”
Section: Planetary Wave Effectmentioning
confidence: 99%